La comprensión lectora y el rendimiento escolar - García García, Miguel Angel; Arévalo Duarte, Mayra Alejandra; Hernández Suárez, César Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Páginas 152-170.